Placebo and the law of identification - Bierman, Steve F.; Weil, Andrew; Dahmer, Stephen (Frontiers in Psychiatry, 2024)
Thousands of essays and studies have been published on placebo and nocebo. Yet, despite this plethora of information, we are not much closer to a comprehensive understanding of the fundamental mechanism producing placebo and nocebo effects than we were in 1946, when participants in the Cornell Conferences on Therapy speculated on the roles of authority, belief and expectancy. In this paper, we examine the weaknesses in current placebo and nocebo definitions and theories. We also propose a more concise and comprehensive definition and theory of placebo and nocebo by introducing the Law of Identification and the Generic Placebo Instruction (GPI). The latter being the placebo/nocebo information expressed or implied in virtually every clinical encounter and trial; the former (i.e., the Law of Identification), being what drives the GPI to actualization. Further, we demonstrate the explanatory power of this new theory and suggest clinical studies that test predictions arising from it - studies whose results, if positive, would translate universally into clinical practice.